PENERAPAN TEORI BELAJAR KOGNITIF DALAM PEMBELAJARAN DASAR DI SDN 33 RAWANG BARAT - Dewi Fitriana; Mardona Putra; Anja Kesuma Putri; Hosman; Nur Washli; Anggia Ekasari; Nanang Ady Saputra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to explore the application of cognitive learning theories, specifically Gestalt theory, Ausubel's theory, and constructivism, in teaching at SDN 33 Rawang Barat. These theories are implemented to enhance students' understanding and engagement in the learning process. This research employs a qualitative approach with empirical observation, interviews with teachers, and analysis of teaching materials. The findings show that despite challenges in time management, resource limitations, and diverse student abilities, the application of these cognitive theories significantly impacts students' understanding. Teachers who successfully implement these approaches create more meaningful, interactive, and real-life relevant learning experiences. This study suggests that teachers continue to deepen their understanding of cognitive learning theories and focus more on adapting teaching methods to the diverse needs of students.